2022
DOI: 10.3390/jcm11092615
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Colchicine in the Treatment of COVID-19 Patients: A Systematic Review and Meta-Analysis

Abstract: Objective: We assessed the efficacy of colchicine in COVID-19 patients through a systematic review. Methods: Six databases were searched until March 2022 for studies assessing colchicine versus control in hospitalized patients with COVID-19. The primary outcome was mortality, and secondary outcome was length of hospitalization. Inverse variance and random effect meta-analyses were performed. The strength of evidence was assessed using GRADE. Results: Nine studies (five randomized clinical trials (RCTs) and fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 32 publications
2
16
0
Order By: Relevance
“…The beneficial effects seemed to occur within the first 72 h, concurrently with a significant reduction in serum CRP. Although our and other groups have found beneficial effects of colchicine in COVID-19 patients, a greater number of studies failed to demonstrate a reduction in hospitalization, intensive care unit admission, or mortality, as reviewed in meta-analyses [9][10][11], which concluded that colchicine is not beneficial for treatment in outpatient and inpatient settings. Hence, colchicine is currently not indicated for COVID-19 [12][13][14].…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…The beneficial effects seemed to occur within the first 72 h, concurrently with a significant reduction in serum CRP. Although our and other groups have found beneficial effects of colchicine in COVID-19 patients, a greater number of studies failed to demonstrate a reduction in hospitalization, intensive care unit admission, or mortality, as reviewed in meta-analyses [9][10][11], which concluded that colchicine is not beneficial for treatment in outpatient and inpatient settings. Hence, colchicine is currently not indicated for COVID-19 [12][13][14].…”
Section: Introductionmentioning
confidence: 85%
“…The first studies evaluating the effect of colchicine on COVID-19 showed its utility in controlling systemic inflammation caused by SARS-CoV-2, resulting in shorter hospital stays and lower mortality [16]. Initial observations were followed by a greater number of studies, observational or controlled, in which this effect of colchicine was not confirmed by the majority [9][10][11]. Moreover, the two most prominent studies on colchicine for COVID-19, one recruiting outpatients [17] and the other recruiting inpatients [18], failed to demonstrate the efficacy of colchicine for their primary endpoints.…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review and meta-analysis by Yasmin et al [ 75 ] involved randomized clinical trials regarding the safety and effectiveness of colchicine in COVID-19 patients demonstrating that colchicine was effective and safe in the management of COVID-19. However, another systematic review illustrated that colchicine was infective in reducing mortality of hospitalized COVID-19 patients [ 76 ].…”
Section: Modulation Release Of Gdf15mentioning
confidence: 99%
“…Colchicine has a variety of off-label uses, including pericarditis, various dermatologic disorders, Behçet’s disease, and more recently it has been used to reduce cardiovascular events in patients with coronary artery disease [ 1 4 ]. Colchicine has also been tested in patients with COVID-19 in numerous clinical trials, but the results to date have been disappointing [ 5 , 6 ]. Colchicine is still under investigation for treatment of long COVID [ 7 ], and it can be used to treat the pericarditis that can occur in COVID patients [ 8 ].…”
Section: Introductionmentioning
confidence: 99%